Possibilities and features of zero-ischemia nephron-sparing surgery in localized kidney cancer - A. V. Seregin; O. B. Loran; A. A. Seregin; N. A. Shustitskiy; I. V. Seregin; O. V. Bessolova; T. R. Indarokov (Вестник урологии)
Kidney cancer (KCa) is one of the greatest challenges in oncological urology due to the increase in morbidity and mortality rates annually. In the treatment of KCa, preservation of renal function is an important objective, in addition to achieving oncological results. The article presents the experience of treatment of 175 KCa-patients of pT1a – T2aN0M0 stages, who underwent nephron-saving surgery (NSS) with preventive hemostatic sutures. Functional outcomes of NSS were studied in the groups without cross-linking (group 1; n = 150) and with cross-linking of the renal pedicle (group 2; n = 25). Kidney resection with prophylactic suturing has been shown to allow removal of a tumour of almost any localisation. By avoiding cross-linking of the renal pedicle during surgery, post-ischemic changes in the renal parenchyma are minimised. Thus, one month after surgery, the perfusion indexes in groups 1 & 2 were 45.2 ± 3.0% vs 35.5 ± 3.3%; renal indexes were 44.8 ± 2.4% vs 39.1 ± 1.4%; areas of the functioning parenchyma were 52.0 ± 10.0% vs 35.0 ± 9.0%, respectively.